Effect of sowing technology on the yield and harvest grain moisture content of maize (Zea mays L.) hybrids with different genotypes - Murányi, Eszter (Acta Agraria Debreceniensis, 2016)
From the aspect of the efficiency of maize production harvest grain moisture content shall be considered beside the amount of harvested grain yield. Hybrids with different genotypes and vegetation period length lose their moisture content different that is affected by row spacing and plant density – among agrotechnical production factors – depending on the given crop year. In the present research work three crop years with different weather conditions were studied (2013, 2014, and 2015). The small-plot field experiment was set up at the Látókép Field Research Centre of the University of Debrecen, Centre for Agricultural Sciences with four replications on a chernozem soil type. The effect of three factors was analysed in the experiment on yield amount and its moisture content. Factors were row spacing (45 and 76 cm), plant density (50, 70 and 90 thousand plants ha-1), while hybrids were of very early (Sarolta: FAO 290), early (DKC 4014: FAO 320, P 9175: FAO 330, P 9494: FAO 390) and medium (SY Afinity: FAO 470) ripening.In the crop year of 2013 the highest yield was produced – regarding the average of the hybrids – by the application of a row spacing of 45 cm (4.5%, 673 kg ha-1), however there was no significant difference between the yield of the populations of different row spacings. Significant difference (14.9%, 1751 kg ha-1; 6.3%, 583 kg ha-1) could be found in case of yield between different row spacing applications in 2014 and 2015. The effect of insufficiently distributed low amount of precipitation and lasting heat days in 2015 could be revealed in yield amounts and harvest grain yield moisture content results that were lower than in the previous years. In 2015 grain yield moisture content varied between 10.3 and 13.9% in case of a row spacing of 45 cm, while by 76 cm between 11.0 and 13.9%.